N-Methyl D-Aspartate Receptor Antagonist Kynurenic Acid Affects Human Cortical Development - Bagasrawala, Inseyah; Zecevic, Nada; Radonjić, Nevena V. (Frontiers in Neuroscience, 2016)
Kynurenic acid (KYNA), a neuroactive metabolite of tryptophan degradation, acts as an endogenous N-methyl-D-aspartate receptor (NMDAR) antagonist. Elevated levels of KYNA have been observed in pregnant women after viral infections and are considered to play a role in neurodevelopmental disorders. However, the consequences of KYNA-induced NMDAR blockade in human cortical development still remain elusive. To study the potential impact of KYNA on human neurodevelopment, we used an in vitro system of multipotent cortical progenitors, i.e., radial glia cells (RGCs), enriched from human cerebral cortex at mid-gestation (16-19 gestational weeks). KYNA treatment significantly decreased RGCs proliferation and survival by antagonizing NMDAR. This alteration resulted in a reduced number of cortical progenitors and neurons while number and activation of astrocytes increased. KYNA treatment reduced differentiation of RGCs into GABAergic neurons, while differentiation into glutamatergic neurons was relatively spared. Furthermore, in mixed cortical cultures KYNA triggered an inflammatory response as evidenced by increased levels of the pro-inflammatory cytokine IL-6. In conclusion, elevated levels of KYNA play a significant role in human RGC fate determination by antagonizing NMDARs and by activating an inflammatory response. The altered cell composition observed in cell culture following exposure to elevated KYNA levels suggests a mechanism for impairment of cortical circuitry formation in the fetal brain after viral infection, as seen in neurodevelopmental disorders such as schizophrenia.